Subsidising car purchases in the euro area: Any spill-over on production? - Joan Paredes (European Central Bank (ECB), 2017)
Due to input-output linkages, an industry level shock can widely transmit to the rest of the economy. We identify government policies on the automobile industry, which change final prices and estimate their effect on sales and production. An example could be the scrappage schemes that many European governments introduced at the start of the Great Recession. In line with previous studies, we confirm that the effect on car sales is positive. More interestingly, we extend the literature that explores the effects of these policies on domestic and foreign production to disentangle the potential spill-overs.
Keywords: C32; C54; E23; E62; H25; 330; Bayesian GVAR; Fiscal Policy; Production; Automotive Industry; Spill-overs